2010
DOI: 10.1007/s00199-010-0585-3
|View full text |Cite
|
Sign up to set email alerts
|

Ownership structure and efficiency in large economies

Abstract: We analyze the limit behavior of sequences of oligopolistic equilibria in which firms follow objectives consistent with their shareholders' interests. We show that the efficiency of the limit allocation depends on how firms' shares are distributed across consumers, and provide a characterization of the class of ownership structures that lead to Walrasian equilibrium allocations in the limit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…However, there is a lack of extant literature on exploring the governance mechanisms of zombie firms from the perspective of ownership structure. It has been demonstrated that ownership structure has a significant impact on corporate behaviour and strategic decision‐making (Fan and Wong, 2002; Bejan and Bidian, 2012; McGuinness et al, 2017). Combined with the emerging phenomenon of common institutional ownership in recent years, we find that common institutional ownership plays a synergistic governance role and thus inhibits the formation of zombie firms.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, there is a lack of extant literature on exploring the governance mechanisms of zombie firms from the perspective of ownership structure. It has been demonstrated that ownership structure has a significant impact on corporate behaviour and strategic decision‐making (Fan and Wong, 2002; Bejan and Bidian, 2012; McGuinness et al, 2017). Combined with the emerging phenomenon of common institutional ownership in recent years, we find that common institutional ownership plays a synergistic governance role and thus inhibits the formation of zombie firms.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Furthermore, various researchers such as Williamson (1964), Marris (1964), Galbraith (1967), Pfeffer and Salancik (1978), Salami (2011), Su and He (2012), Bejan and Bidian (2012) have argued that ownership structure has important implications for firm efficiency and strategic development. Based on the principal-agency problem model, Jensen and Meckling (1976) have argued that a firm's performance will be negatively related to low ownership concentration and positively related to high ownership concentration.…”
Section: Literature Reviewmentioning
confidence: 99%